Perceiving college peers' alcohol consumption: temporal patterns and individual differences in overestimation. Issue 2 (1st February 2019) - Giese, Helge; Stok, F. Marijn; Renner, Britta
Abstract: Objective: This study examines temporal patterns and individual differences of overestimation in alcohol norm perception within a social network. Design: Hundred psychology freshmen indicated biweekly during their first semester the drinks they consumed, the perceived average of their peers' consumption, and with whom they were acquainted. At baseline, trait self-control was assessed. Main outcome: The moderation of alcohol consumption overestimation by time and individual characteristics was explored. Results: Results show that students overestimated alcohol consumption of their acquainted peers by 1.22 drinks ( p  < .001). For time periods at which peers reported high consumption, overestimation decreased. Additionally, individuals reporting high alcohol consumption ( b  = −0.25, p  < .001) and low self-control ( b  = 0.27, p  = .010) showed higher overestimation. Conclusions: Students overestimate the alcohol consumption of peers not fully accounting for changes in peer-reports. Furthermore, individual differences suggest informational and motivational processes underlying overestimation.